Untargeted LC–MS/MS-Based Metabolomic Profiling for the Edible and Medicinal Plant Salvia miltiorrhiza Under Different Levels of Cadmium Stress - Yuan, Jun; Liu, Rongpeng; Sheng, Shasha; Fu, Haihui; Wang, Xiaoyun (Frontiers in Plant Science, 2022)
Salvia miltiorrhiza, a medicinal and edible plant, has been extensively applied to treat cardiovascular diseases and chronic hepatitis. Cadmium (Cd) affects the quality of S. miltiorrhiza, posing serious threats to human health. To reveal the metabolic mechanisms of S. miltiorrhiza’s resistance to Cd stress, metabolite changes in S. miltiorrhiza roots treated with 0 (CK), 25 (T1), 50 (T2) and 100 (T3) mg kg-1 Cd by liquid chromatography coupled to mass spectrometry (LC–MS/MS) were investigated. A total of 305 metabolites were identified, and most of them were amino acids, organic acids and fatty acids, which contributed to the discrimination of CK from the Cd-treated groups. Among them, S. miltiorrhiza mainly upregulated o-tyrosine, chorismate and eudesmic acid in resistance to 25 mg kg-1 Cd; DL-tryptophan, L-aspartic acid, L-proline and chorismite in resistance to 50 mg kg-1 Cd; and L-proline, L-serine, L-histidine, eudesmic acid, and rosmarinic acid in resistance to 100 mg kg-1 Cd. It mainly downregulated unsaturated fatty acids (e.g., oleic acid, linoleic acid) in resistance to 25, 50 and 100 mg kg-1 Cd and upregulated saturated fatty acids (especially stearic acid) in resistance to 100 mg kg-1 Cd. Biosynthesis of unsaturated fatty acids, isoquinoline alkaloid, betalain, aminoacyl-tRNA, and tyrosine metabolism were the significantly enriched metabolic pathways and the most important pathways involved in the Cd resistance of S. miltiorrhiza. These data elucidated the crucial metabolic mechanisms involved in S. miltiorrhiza Cd resistance and the crucial metabolites that could be used to improve resistance to Cd stress in medicinal plant breeding.